Family Communication & Young Adult Decision-Making : Who Influences Whom? - Miniatt, Elizabeth; Engstrom, Sarah; Von Feldt, Krista; Stone, Mikayla; Knutson, Kristine; Jungquist, Elizabeth; Fay, Martha (My University, 2018)
Family communication has long been associated with young adult decision-making found that frequent, open, honest communication between parents and children is a significant predictor of parental influence on young adult decision making. Sullivan & Sullivan (1980) found that when children leave home there is an increase in open communication between parents and children. This study examines the association between family communication and young adult decision-making with regard to when particular decisions are made and personal ideologies solidified. Socialization research and Intergenerational Transmission theory assume that the direction of influence is parent to child, and much of the research reflects this. This study examines whether young adults believe they influence their parents through their communication about ideologies. Results will extend knowledge of family communication patterns and add to understanding in the area of direction of influence.
Color poster with text and graphs.
Keywords: Young adults; Families; Communication; Posters